A numerical review of three Basque dialects - Jansen, Wim (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 1990)
An attempt is made to establish some quantitative affinity relations among three (sub)dialects of Basque: the Aezcoan variety of Western Low-Navarrese (A), the Salazarese variety of Eastern Low-Navarrese (S), and the now extinct Roncalese dialect (R). The study is based on L. Michelena’s "Un vocabulario aezcoano, salacenco y roncalés preparado por el Príncipe Bonaparte" (BAP 1958, reprinted in SHLV) as the only source of information. The areas occupied by the three varieties of Basque are shown in figure 1. In this figure the Aezcoan area is delimited by the dotted line around the towns of Abaurrea Alta, Abaurrea Baja, Aria, Arive, Garayoa, Garralda, Orbaiceta, Orbara and Villanueva. The Salazarese area is taken around the towns of Escároz, Esparza, Izalzu, Jaurrieta, Ochagavía and Oronoz. The dotted line around Garde, Isaba, Roncal, Uztárroz, Urzainqui and Vidangoz defines the Roncalese dialect area. In reality the three areas are contiguous. In this context, however, they are shown as three separate dialect, islands, thus allowing a better pictorial representation of the numerical results of the study.